Dual mtor/dna-pk inhibitor cc-115 induces cell death in melanoma cells and has radiosensitizing potential - Bürkel, Felix; Jost, Tina; Hecht, Markus; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
CC-115 is a dual inhibitor of the mechanistic target of rapamycin (mTOR) kinase and the DNA-dependent protein kinase (DNA-PK) that is currently being studied in phase I/II clinical trials. DNA-PK is essential for the repair of DNA-double strand breaks (DSB). Radiotherapy is frequently used in the palliative treatment of metastatic melanoma patients and induces DSBs. Melanoma cell lines and healthy-donor skin fibroblast cell lines were treated with CC-115 and ionizing irradiation (IR). Apoptosis, necrosis, and cell cycle distribution were analyzed. Colony forming assays were conducted to study radiosensitizing effects. Immunofluorescence microscopy was performed to determine the activity of homologous recombination (HR). In most of the malign cell lines, an increasing concentration of CC-115 resulted in increased cell death. Furthermore, strong cytotoxic effects were only observed in malignant cell lines. Regarding clonogenicity, all cell lines displayed decreased survival fractions during combined inhibitor and IR treatment and supra-additive effects of the combination were observable in 5 out of 9 melanoma cell lines. CC-115 showed radiosensitizing potential in 7 out of 9 melanoma cell lines, but not in healthy skin fibroblasts. Based on our data CC-115 treatment could be a promising approach for patients with metastatic melanoma, particularly in the combination with radiotherapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA repair; DNA-PK; Homologous recombination (HR); Kinase inhibitor; Melanoma; MTOR; Non-homologous end-joining (NHEJ); Radiosensitivity